(3MQcI GdJbOe GdJbfj GROgGQ Ce GfgjGQ GdQCSeGdjI ?s - (3fGOQ GOQjS(B, (3GdJds ((3YeGf(B:s (3OGQ GdcJGH GdMOjK(B,s, 2012)
(3GdJbOe GdJbfj h GdQCSeGdjI h MQcI GdGbJUGO aj GdHdOGf GdfGejI h eTcdGJ Gdfeh h GdJWhQ aj GWGQ GdYdGbGJ GdQCSeGdjI h fXQjI GdbjeI eY JfGhd GdGTJQGcjIs
(3bGFeI GdLOGhd U(B.7s
Keywords: (3EbJUGO GdShbs; (3GdQCSeGdjIs